Photorefractive Keratectomy on Purely Refractive Accommodative Esotropia. (January 2015) - Rossi, Settimio; Testa, Francesco; Santamaria, Carmine; Orrico, Ada; Attanasio, Marcella; Simonelli, Francesca; De Rosa, Guiseppe
Abstract Context: Results on refractive keratectomy of the treatment of young patients with purely refractive accommodative esotropia. Aims: Evaluating the results of refractive keratectomy (PRK) on the treatment of young patients with purely refractive accommodative esotropia. Methods and Material: This prospective study comprised patients with purely accommodative hyperopic esotropia. Patients underwent a complete ophthalmologic examination that included pre-operative and post-operative best corrected visual acuity (BCVA) and uncorrected visual acuity (UCVA) (at 3, 12, and 24 months), alignment and sensory outcomes; keratometry, pachymetry, and corneal topography. Statistical analysis used: paired T-student. Results: Twenty eyes of 10 patients (mean age 21.5 years) were treated. The pre-operative mean UCVA was 0.70 logMAR (SD ± 0.177) and 0.02 logMAR (SD ± 0.029) two years later. The pre-operative BCVA was 0.02 logMAR (SD ± 0.037) and 0.01 (SD ± 0.026) two years later. The mean spherical equivalent (SE) in cyclopegia was + 3.92 D (range: +2.75 to +5.00 D; SD = 0.62) pre-operatively, −0.69 D (range −0.5 to −1) at three months and 0 D (range: −0.25 to 0.25) at one and two years later. After surgery, all patients were orthophoric without correction and stereopsis was unaffected by PRK. Conclusions: A two-year follow-up showed that photorefractive keratectomy was an effective treatment for esotropia associated with mild to moderate hyperopia in young adults with purely refractive accommodative esotropia.